Personaliti Warna Menurut Teori Don Lowry Dalam Seramik Kontemporari - Jalwa Jazilah, Binti Mohamad Rosdi (Universiti Malaysia Sarawak(UNIMAS), 2018)
Colour has an important role in human life, through our colours to recognize one's personality. Colour is also something that can not be seen but can see and give psychological impression to humans. The creator produce works from the collection of questionnaire data to recognize the personality of students aged 21-24 at Universiti Malaysia Sarawak. To know the meaning behind the color personality of the students, researchers use the theory of Don Lowry. However, researchers have used the method from Sidek Mohd Noah to identify the color of student personality at Unimas. Researchers have used a method called Color Personality Inventory (IPW). The main media in this work is ceramic. The results of this study will be applied to contemporary ceramics.